The role of glycogen and lactate in supporting action potential conduction in mouse central white matter and peripheral nerve - Evans, Richard Debney (2012)
Central white matter and peripheral nerves function by conducting action potentials, which rely on the presence of transmembrane potentials generated by ion gradients. The maintenance of these transmembrane potentials is the main energy-dependent process in the nervous system. In this thesis I investigated the ability of endogenous glycogen to support the energy requirements of nervous tissue and the role of lactate in this process. Glycogen in the CNS is located in astrocytes but is capable of supporting axonal conduction, implying axon-glial metabolic interactions. These interactions were investigated in both the mouse optic nerve (MON), a central white matter tract, and the mouse sciatic nerve (MSN), a mixed peripheral nerve. Electrophysiological techniques were used to record action potential conduction in the nerves as an index of nerve function. Parallel experiments to quantify glycogen content using biochemical assay, or simultaneous real-time measurement of lactate release from the nerves using enzyme-based lactate biosensors, correlated action potential conduction with glycogen content, or lactate release, respectively. Depletion of glycogen leaves the MON vulnerable to irreversible injury to a greater extent than exposure to moderate hyperthermia during aglycemia. Glycogen also greatly enhanced the neuroprotective effects of mild hypothermia during aglycemia. Under resting conditions lactate in the immediate vicinity of the MON was stable at ~0.5 mM, a concentration that increased with axonal activity, dependent upon stimulus intensity. Raising extracellular K+ evoked lactate release, suggesting that increased neuronal activity promotes lactate release. Inhibition of glycogen metabolism, partly reduced lactate release from the MON, implying that glycogen metabolism is important under normal physiological conditions. The relative contribution of glycogen to lactate release increased with axonal activity, consistent with activity-induced glycogenolysis. These studies were then extended to the peripheral nervous system as the role of glycogen in this tissue has not previously been considered. Glycogen, which was present in Schwann cells, supported myelinated, but not un-myelinated axons during aglycemia, suggesting a more complex and selective neuroprotective role than that in central white matter.